Avaliação das vias de sinalização induzidas pela molécula orientadora a (RGMa) solúvel durante a miogênese in vitro - Alinne do Carmo Costa (2018)
RGMa is one of the members of the Repulsive Guidance Molecule (RGM) family, that were initialy found playing roles as clues to guide axon migration. Recent new studies have been pointing to a higher range of biological functions for these molecules, including during myogenesis. Previous in vitro works revealed that the RGMa over-expression induces skeletal muscle cell hyperplasia and hypertrophy. However, the molecular mechanisms used by RGMa to induce these important skeletal muscle effects were not elucidated thus far. In other cell types, RGMa was found to sinalize via Neogenin receptor or as correceptors of the BMP signaling pathway; both of these paths were independently associated with muscle phenotypes similar to the ones we have observed for RGMa. In this work, RGMa administrated as recombinant protein to C2C12 mioblasts in terminal differentiation stage induced hyperplasia (higher fusion index) and differentiation of these cells. If administrated during the initial stages of differentiation, however, RGMa treatment can induce differentitation only. RGMa treatment of mioblasts under the effect of a BMP signaling inhibitor drug could potencialize its effects on hyperplasia; while RGMa treatment of mioblasts that were induced to over-express the receptor Neogenin could induce the expression of myogenic differentiation markers. Besides, the RGMa treatment of mioblasts in growth medium could induce a higher viability index; while in differentiation medium, the viability index was lower in the treated cells. Therefore, these results suggest that recombinant RGMa can induce both hyperplasia and skeletal muscle differentiation; the skeletal muscle hyperplasia effects induced by RGMa is BMP-independent; and that RGMa effects on myogenic differentiation are induced via Neogenin pathway. Genes associated with skeletal muscle development are sources for gene therapies to treat a number of myopathies and can also be used in genetic breeding programs.